2017
DOI: 10.1371/journal.pone.0176275
|View full text |Cite
|
Sign up to set email alerts
|

Initial assessment of the infant with neonatal cholestasis—Is this biliary atresia?

Abstract: IntroductionOptimizing outcome in biliary atresia (BA) requires timely diagnosis. Cholestasis is a presenting feature of BA, as well as other diagnoses (Non-BA). Identification of clinical features of neonatal cholestasis that would expedite decisions to pursue subsequent invasive testing to correctly diagnose or exclude BA would enhance outcomes. The analytical goal was to develop a predictive model for BA using data available at initial presentation.MethodsInfants at presentation with neonatal cholestasis (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 31 publications
1
46
0
1
Order By: Relevance
“…Early HPE is associated with an increased probability of a jaundice‐free status 3 months postsurgery, as well as better clinical outcomes, but accurately diagnosing BA in cholestatic infants remains challenging . A recent multicenter study using the classification and regression decision tree (CART) predictive model reported an 81% true‐positive rate and an 11% false‐negative rate for BA . Despite the high accuracy of the optimized prediction models in the CART study, the high precision required for differentiating BA was not achieved .…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Early HPE is associated with an increased probability of a jaundice‐free status 3 months postsurgery, as well as better clinical outcomes, but accurately diagnosing BA in cholestatic infants remains challenging . A recent multicenter study using the classification and regression decision tree (CART) predictive model reported an 81% true‐positive rate and an 11% false‐negative rate for BA . Despite the high accuracy of the optimized prediction models in the CART study, the high precision required for differentiating BA was not achieved .…”
Section: Discussionsupporting
confidence: 63%
“…A recent multicenter study using the classification and regression decision tree (CART) predictive model reported an 81% true‐positive rate and an 11% false‐negative rate for BA . Despite the high accuracy of the optimized prediction models in the CART study, the high precision required for differentiating BA was not achieved . Liver biopsy may assist in the diagnosis and assessment of LF status in cholestatic infants, but is invasive.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations